2015
DOI: 10.2147/ndt.s87614
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention-deficit hyperactivity disorder, risky behaviors, and motorcycle injuries: a case-control study

Abstract: BackgroundThe aim of this study was to assess the association of motorcycle traffic injuries with motorcycle riding behavior and subtypes of attention-deficit hyperactivity disorder (ADHD) while controlling for individual correlates of motorcycle traffic injuries.MethodsA case-control study was carried out in 298 patients with motorcycle trauma along with 151 control patients admitted to the Shohada and Imam Reza university hospitals as the two referral specialty centers in the East Azarbyjan Province of Iran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…The sample size was calculated utilizing the information on the main outcome, the relation between MRB and ADHD, and the information was attained from the study by Abedi et al (Sadeghi-Bazargani et al, 2015a). By the confidence level of 95 and 80% power, 227 subjects were estimated to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size was calculated utilizing the information on the main outcome, the relation between MRB and ADHD, and the information was attained from the study by Abedi et al (Sadeghi-Bazargani et al, 2015a). By the confidence level of 95 and 80% power, 227 subjects were estimated to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the study by Özkan et al (2012), higher scores on the speed violations and the stunts scales of MRB were significantly related to more self-reported offenses (Özkan et al, 2012). The other studies reported the same set of predictors and mainly ADHD (and the subscales) as the determinates of risky riding behavior in Iran (Sadeghi-Bazargani et al, 2015b, Sadeghi-Bazargani et al, 2019, Safiri et al, 2013. MRB may intentionally or unintentionally lead to or prevent RTA (Haque et al, 2010, Stephens et al, 2017, Truong et al, 2018.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Based on a systematic review, people with ADHD are more likely to be injured; the risk is reported as two-fold. 12 Considering that there is no similar study in the region, if this study shows a relationship between the severity of trauma and ADHD symptoms in children, the next step will be conduction of a research on making home and school settings safe for them. Since trauma is related to road accidents, this study can lay the ground for further investigations and enrich the existing knowledge.…”
Section: Introductionmentioning
confidence: 99%